Developing and implementing a culturally informed FAmily Motivational Engagement Strategy (FAMES) to increase family engagement in first episode psychosis programs: mixed methods pilot study protocol. Issue 8 (26th August 2020) - Oluwoye, Oladunni; Dyck, Dennis; McPherson, Sterling M; Lewis-Fernández, Roberto; Compton, Michael T; McDonell, Michael G; Cabassa, Leopoldo J
Abstract : Introduction: Despite the proven effectiveness of coordinated specialty care (CSC) programmes for first episode psychosis in the USA, CSC programmes often have low levels of engagement in family psychoeducation, and engagement of racial and ethnic minority family members is even lower than that for non-Latino white family members. The goal of this study is to develop and evaluate a culturally informed FAmily Motivational Engagement Strategy (FAMES) and implementation toolkit for CSC providers. Methods and analysis: This protocol describes a mixed methods, multi-phase study that blends intervention mapping and the Promoting Action on Research in Health Services framework to develop, modify and pilot-test FAMES and an accompanying implementation toolkit. Phase 1 will convene a Stakeholder Advisory Committee to inform modifications based on findings from phases 1 and 2. During phase 1, we will also recruit approximately 200 family members to complete an online survey to assess barriers and motivation to engage in treatment. Phase 2 we will recruit five family members into a 3-month trial of the modified FAMES and implementation toolkit. Results will guide the advisory committee in refining the intervention and implementation toolkit. Phase 3 will involve a 16-month non-randomised, stepped-wedge trial with 50 family members from five CSC programmes in community-based mental health clinics to examine the acceptability, feasibility and initial impact of FAMES and the implementation toolkit. Ethics and dissemination: This study received Institutional Review Board approval from Washington State University, protocol #17 812–001. Results will be disseminated via peer review publications, presentations at national and international conferences, and to local community mental health agencies and committees. Trial registration number: ClinicalTrials.gov Registry (NCT04188366 ).